2017
DOI: 10.1590/2318-0331.011716074
|View full text |Cite
|
Sign up to set email alerts
|

Climate changes impact estimation on urban drainage system located in low latitudes districts: a study case in Fortaleza-CE

Abstract: The observed changes in extreme weather events reflect the influence of climate change caused by anthropogenic factors, in addition to natural climate variability. According to future climate projections, the increase in the average surface temperature will cause major changes in the average annual rainfall of almost the entire planet. The primary objective of this study is to evaluate the impact of possible scenarios of climate change on urban drainage system in locations situated at low latitudes. The specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
(9 reference statements)
0
12
0
1
Order By: Relevance
“…With respect to precipitation data, Figure 4 shows the results of the optimization process of the Gumbel model for annual maximum precipitation data observed in the region of Ribeirão Preto/SP, published and kindly provided by Penner and Lima (2016). The simulation obtained in this study ( 2 R =0.915) provides values that are similar to those obtained by Penner and Lima (2016), who used Chow's frequency factors to determine the precipitation height for each return period. Figure 5 shows a plot of the variation of the objective function along the generations for the simulation of Figure 2.…”
Section: Global Optimizationmentioning
confidence: 52%
See 2 more Smart Citations
“…With respect to precipitation data, Figure 4 shows the results of the optimization process of the Gumbel model for annual maximum precipitation data observed in the region of Ribeirão Preto/SP, published and kindly provided by Penner and Lima (2016). The simulation obtained in this study ( 2 R =0.915) provides values that are similar to those obtained by Penner and Lima (2016), who used Chow's frequency factors to determine the precipitation height for each return period. Figure 5 shows a plot of the variation of the objective function along the generations for the simulation of Figure 2.…”
Section: Global Optimizationmentioning
confidence: 52%
“…The values listed in Table 6 may be altered if the user wishes to use wider or closer bounds. Illustratively, the system described is then used to determine the IDF curves outlined by Penner and Lima (2016). Figure 6a presents IDF curves in semi-logarithmic scale for three return periods: 5, 25, and 100 years.…”
Section: Toolbox Idfmentioning
confidence: 99%
See 1 more Smart Citation
“…Both global progressive urbanization and climate change [6] have a negative impact on the efficiency of the functioning of sewerage systems, causing more and more frequent overloads leading to local flooding or urban flooding [16,17]. In Poland, an atlas of rains intensities (PANDa) will be created soon.…”
Section: Instead Of a Conclusionmentioning
confidence: 99%
“…Considering the current knowledge of the future trends in climate change [3][4][5][6][7][8][9], the design rainfalls can be adjusted to terrain drainage dimensioning ( Table 1 and Table 3) by correcting the current rainfall intensities or by changing the frequencies of their occurrence in the future. In [10] it was shown that today's rainfall events with a statistical repeatability of, e.g., five years, in the future will be events with a frequency of occurrence C = 2 years.…”
Section: Introductionmentioning
confidence: 99%